Hans Singer's legacy: the problem of commodity exporters revisited - Deutsches Institut für Entwicklungspolitik (DIE) (Deutsches Institut für Entwicklungspolitik (DIE), 2009)
The first Hans Singer Memorial Lecture by Paul Collier on “Hans Singer's legacy: The problem of commodity exporters revisited” took place on 18 May 2009 in Bonn. Hans Singer combined in high measure three roles that today are seldom found together. He was, of course, a researcher: it is his most celebrated research that will be the subject of my talk. But he was also deeply engaged in the world of policy. When Hans Singer studied for his doctorate this was indeed a combination to which many economists aspired: his supervisor, John Maynard Keynes, provided the perfect model. Like Keynes, Hans Singer focused his research on matters of urgent public policy, and wrote to address a wide audience. Today, much of that has been lost: academic economists write for each other and have manifestly become too detached from policy. But Hans Singer's third role should also be recognized: he built organizations, first at the United Nations and then at the Institute for Development Studies (IDS). Building organizations takes flair and persistence. In the academic world such characteristics are rare: academics tend to be drawn from that part of the population that is clever but incompetent and so few manage to leave a legacy beyond ideas. That combination – research, policy, and organization-building – was what makes Hans Singer a role model.
Keywords: 330